The Role of Distance Learning in Shaping Indonesia Golden Generation: Student Interaction, Engagement, and Satisfaction - Suseno, Giri; Hendarti, Titin; Ramadani, Suci Putri (Journal of Education and Teaching Learning, 2024)
This research explores the critical role of student interaction in enhancing engagement and satisfaction in the context of Open and Distance Learning (ODL) at the Open University in Indonesia. Amidst the increasing adoption of digital education platforms, this study examines how dynamic and effective student interactions and engagement influence educational satisfaction outcomes in online environments. Using a quantitative approach, this study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyse responses from 120 students who participated in online tutorial sessions. The findings reveal that student interaction significantly increases student satisfaction and engagement, with engagement serving as a mediating factor that improves the overall educational experience. This study confirms that high-quality interactions are essential for student engagement and satisfaction and emphasises the need for educational platforms that support strong interactive features and prompt instructor feedback. This research contributes to the literature by emphasising the important role of interaction and engagement in ODL settings and suggests practical implications for educational practitioners and policy makers. Enhancing interactive experiences in online learning can facilitate higher levels of student engagement and satisfaction, thereby supporting the formation of a competitive and adaptive golden generation in Indonesia's digital era.